Advancements in Hepatocellular Carcinoma: Potential Preclinical Drugs and their Future - Butt, Noor-ul-Huda; Baytas, Sultan N. (Current Pharmaceutical Design, 2023)
Hepatocellular carcinoma (HCC) is one of the foremost causes of tumor-affiliated demises globally. The HCC treatment has undergone numerous developments in terms of both drug and non-drug treatments. The United States Food and Drug Administration (FDA) has authorized the usage of a variety of drugs for the treatment of HCC in recent years, involving multi-kinase inhibitors (lenvatinib, regorafenib, ramucirumab, and cabozantinib), immune checkpoint inhibitors (ICIs) (pembrolizumab and nivolumab), and combination therapies like atezolizumab along with bevacizumab. There are currently over a thousand ongoing clinical and preclinical studies for novel HCC drugs, which portrays a competent setting in the field. This review discusses the i. FDA-approved HCC drugs, their molecular targets, safety profiles, and potential disadvantages; ii. The intrial agents/drugs, their molecular targets, and possible benefits compared to alternatives, and iii. The current and future status of potential preclinical drugs with novel therapeutic targets for HCC. Consequently, existing drug treatments and novel strategies with their balanced consumption could ensure a promising future for a universal remedy of HCC in the near future.
Keywords: bevacizumab